Evaluation of Public–Private Partnership in the Veterinary Domain Using Impact Pathway Methodology: In-depth Case Study in the Poultry Sector in Ethiopia - N'Guessan, N'gbocho Bernard; Poupaud, Mariline; Dieuzy-Labaye, Isabelle; Asfaw, Yohannes T.; Wieland, Barbara; Tesfu, Fseha; Daniel, Ulric; Tulayakul, Phitsanu; Peyre, Marisa (Frontiers in Veterinary Science, 2022)
Public-private partnerships (PPPs) in the veterinary domain are joint approaches in which public Veterinary Services and private actors such as private veterinarians, producers’ associations or private companies work together to address complex animal health challenges. They are implemented worldwide and can help to strengthen the capacities of Veterinary Services, but few have been evaluated. None of the evaluations developed in the veterinary domain explicitly addressed PPPs, their complex programme design, their evolving governance, and coordination system, and their impacts. This work represents the first application of the participatory impact pathway methodology for the evaluation of a PPP in the veterinary domain. The public-private partnership evaluated aimed at developing the poultry sector in Ethiopia and improving poultry health service coverage, particularly in remote areas. The combination of semi-structured interviews (n=64) and collective reflection during three workshops (n participants=26, 48, 18), captured the viewpoints of public and private partners, actors who influenced the partnership and actors impacted by it. The context of the public-private partnership was analysed and the causal relationships between the PPP and its impacts were investigated. This work showed that collaboration between the public and private sector occurred at several administrative levels. The actors considered a variety of impacts, on the economy, business, trust and health, which were then measured through different indicators. The actors also identified the added-value of the PPP to enrich those impacts. The participatory impact pathway methodology helped to strengthen the engagement of actors in the public-private partnership and to formulate recommendations at the policy level to favour positive results. This case study represents a milestone in building a participatory evaluation framework of public-private partnership in the veterinary domain.